Constructing multi-type defects in In0.1Sb1.9Te3-(MgB2)x composites: Simultaneously enhancing the thermoelectric and mechanical properties. (December 2021) - Qin, Haixu; Sun, Sibo; Liu, Yuan; Yin, Li; Zhang, Yang; Sun, Yuxin; Xie, Liangjun; Qin, Dandan; Guo, Muchun; Guo, Fengkai; Qu, Wanbo; Liu, Zihang; et al.
Abstract: Nanostructure technologies promote Sb2 Te3 based alloys as powerful candidates for mid-temperature thermoelectric materials, but their actual application needs further breakthrough on both zT value and mechanical properties. Here, we prepare nanostructured In0.1 Sb1.9 Te3 with MgB2 addition, obtaining a high zT value of 1.01 at 673 K with significantly enhanced mechanical strength. It is found that the magnesium dissolves into the matrix lattice, while the boron (B) mainly precipitates out or enters into the van der Waal gaps. Combining with the occurrence of twin and domain boundaries, multi-type defects are constructed to simultaneously adjust the carrier and phonon transport, leading to enhanced power factor and reduced lattice/bipolar thermal conductivity. Meanwhile, the B interstitials and B-rich nanoprecipitates could effectively strengthen the materials. Especially at 673 K, the compressive strength is increased over 600% from < 1 MPa for In0.1 Sb1.9 Te3 to 7.5 MPa for In0.1 Sb1.9 Te3 -(MgB2 )0.015, overcoming the high-temperature softening problem and guaranteeing the service stability. Ultimately, a segmented leg composing of this material and low-temperature ternary alloy (Bi, Sb)2 Te3 is fabricated through simple one-step sintering with a high conversion of 7% under a temperature difference of 375 K. Graphical Abstract: ga1 Highlights: Multi-type defects are constructed in In0.1 Sb1.9 Te3 by MgB2 addition. Thermoelectric and mechanical properties are simultaneously improved. A high average zT value of 1.1 is achieved within 303–673 K. A segmented thermoelectric leg is fabricated with high conversion efficiency of 7%.